Analysis on Internal and External Factor Related to the Performance of Midwives in Neonatal Visits in Pati District - Ferry Rachmawatie Suryaningtyas; Sri Achadi Nugraheni; Atik Mawarni (Jurnal Manajemen Kesehatan Indonesia, 2014)
AbstrakDi Kabupaten Pati Kunjungan Neonatal selama 3 tahun terakhir cenderung mengalami fluktuasi, 93,75% pada tahun 2009, 90,79% pada tahun 2010, dan 97,02% pada tahun 2011. Keadaan ini menunjukkan belum semua bidan desa melaksanakan Kunjungan Neonatal. Tujuan penelitian menganalisis faktor internal dan faktor eksternal yang berhubungan dengan kinerja bidan desa dalam kunjungan neonatal di Kabupaten Pati.Jenis penelitian studi kuantitatif pendekatan cross-sectional. Subjek sejumlah 82 bidan desa yangdipilih secara Cluster Puskesmas. Pengumpulan data dengan wawancara menggunakan kuesioner terstruktur. Data dianalisis secara univariat, bivariat dengan  Chi Square, sedangkan multivariat dengan regresi logistik.Median dan simpang baku umur bidan desa 30 + 5,6 tahun, 91,5% berstatus kawin, median dan simpangan baku masa kerja 5,7 + 4,2 tahun, 70,7% memiliki pengetahuan baik dan sebagian besar 62,2% memiliki motivasi baik. Sebagian besar bidan desa 75,6% menyatakan supervisi baik, 51,2% memiliki persepsi kepemimpinan baik, 56,1% belum pernah mengikuti pelatihan kegawatdaruratan neonatal dan sebagian besar 65,9% menyatakan kompensasi yang diterima baik. Faktor yang berhubungan kinerja adalah umur, masa kerja, pengetahuan, motivasi, supervisi, kepemimpinan, pelatihan, dan kompensasi. Ada pengaruh bersama-sama pengetahuan, supervisi, kompensasi dan motivasi terhadap kinerja bidan desa dalam kunjungan neonatal. Pengetahuan memiliki pengaruh paling kuat terhadap kinerja bidan desa.Disarankan kepada Dinas Kesehatan Kabupaten Pati melaksanakan supervisi sesuai prosedur, menaikkan kompensasi untuk meningkatkan motivasi kerja bidan desa AbstractCoverage of neonatal visit in Pati district in the last 3 years showed fluctuation; 93.75% in 2009, 90.79% in 2010, and 97.02% in 2011. This condition indicated that not all village midwives conducted neonatal visit properly. Objective of this study was to analyze internal and external factors related to the work performance of village midwives in conducting neonatal visits in Pati district. This was an observational-analytical study with cross sectional approach. Study subjects were 82 village midwives selected using clustered random sampling method at primary healthcare center (puskesmas) level. Data were collected through questionnaire. Chi square test and logistic regression were applied in the data analysis. Results of the study showed that median and standard deviation of the age of village midwives were 30 ± 5.6 years old, 91.5% of respondents were married, median and standard deviation of the work period were 5.7 ± 4.2 years, 70.7% of respondents had adequate knowledge, and 62.2% of respondents had good motivation. Majority of village midwives (75.6%) stated that supervision was good, 51.2 % of respondents had good perception on leadership, 56.1% of respondents did not have training experience in the management of neonatal emergency, and 65.9% of respondents stated that they received insufficient compensation. Factors related to the work performance were age, period of work, knowledge, motivation, supervision, leadership, training, and compensation. Factors, in common, affecting the work performance of village midwives in conducting neonatal visit were knowledge, supervision, compensation, and motivation. Knowledge was the strongest factor affecting the work performance of village midwives. Suggestions for Pati district health office are to increase training opportunity for village midwives, to improve supervision, to improve rewards system in order to increase work motivation.